Happy or lonely? Investigating mental well-being using remote methods during the COVID-19 pandemic in The Netherlands (Computational Linguistics in the Netherlands Journal, 2025)
Understanding the unprecedented impact of COVID-19 on mental health and digital interactions is crucial, but also difficult to study in times of physical distancing. This paper contributes to the understanding of well-being in The Netherlands during the pandemic by employing mixed-remote methods. Sentiments of the Dutch public expressed on X (formally Twitter) are analyzed with AI techniques. Additionally, co-creative toolkits and probes, such as diaries, were used with older adults and students for detailed in-situ capturing. The AI approach provides general insights, while toolkit studies can address interpersonal variation and provide non-automated individual feedback. Findings indicate that (1) the pandemic has impacted the expressed emotional states of ‘loneliness’ and ‘happiness’, (2) this varied over time, for example related to pandemic announcements, (3) there are differences between groups (such as young and old), and (4) the toolkits provided contextual self-reflective insights and active inspiration in support of mental well-being.